Experimental Study of Forced- Convection from Horizontal Rectangular Fins Array into Air Duct - Shehab, Saad Najeeb (Al-Khwarizmi Engineering Journal, 2019)
In this work, an experimental study has been done to expect the heat characteristics and performance of the forced-convection from a heated horizontal rectangular fins array to air inside a rectangular cross-section duct. Three several configurations of rectangular fins array have been employed. One configuration without notches and perforations (solid) and two configurations with combination of rectangular-notches and circular-perforations for two various area removal percentages from fins namely 18% notches-9% perforations and 9% notches-18% perforations are utilized. The rectangular fins dimensions and fins number are kept constant. The fins array is heated electrically from the base plate with five different magnitudes of power-inputs. Five several air flow velocity into a duct are utilized. The influence of fin geometry, air flow velocity, Reynolds number and the surface heat flux on the heat-performance of forced heat convection have been simulated and studied experimentally. The experimental data indicates that the combination of 18% rectangular-notched and 9% circular-perforated rectangular fins array gave best forced heat performance in terms of average heat transfer coefficient about (25% - 45%) and (7% - 20%) compared than solid and 9% notches with18% perforations fins array respectively. Five empirical correlations to predict the average Nusselt number for the 18% notches with 9% perforations rectangular fins array at wide range of surface heat flux are deduced. The present data are compared with previous works and a good closeness in behavior is noticed.